Difficulty in diagnosis of nasopharyngeal carcinoma - Siddique, MA; Sabur, MA; Kundu, SC; Mostafa, MG; Khan, JA; Ahmed, S; Karim, MA; Hanif, MA (Mymensingh Medical Journal, 2012)
Mymensingh Med J. 2012 Jan;21(1):158-161 The abstract of this article is available on the PubMed website